Environment & Health: perspectives and challenges - Figueiró, Ronaldo; Arnóbio, Adriano (Revista Práxis, 2013)
The concept of health and environmental health is a historical-conceptual relation with the twentieth century. In this article, environmental health is discussed as a of intersectional and transdisciplinary practices dedicated to the reflections, in human health, of the ecogeossocial relations of man with the environment, aiming well-being, life quality and sustainability, in order to guide public policies formulated using the available knowledge and with social participation and control. In this context, infectious diseases play a key role in the comprehension of environmental health in Brazil and worldwide.